2011
DOI: 10.1007/s10903-011-9505-2
|View full text |Cite
|
Sign up to set email alerts
|

Mobility and HIV in Central America and Mexico: A critical review

Abstract: Mobility is a key determinant of HIV/sexually transmitted infection (STI) transmission dynamics in Asia and Africa. Scant data exist regarding its dynamic impacts on HIV/STI risk in Central America and Mexico. Our objective was to critically review the epidemiology and social and structural context of HIV/STI risk among mobile populations in Central America and Mexico. Eligible articles were published in English or Spanish between January 1, 2000 and August 31, 2010; conducted in Central America or Mexico; spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
71
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 68 publications
(76 citation statements)
references
References 101 publications
2
71
1
Order By: Relevance
“…This difference was not entirely consistent, suggesting that community-level factors shaping the local organisation of sex work in turn shape health behaviours 6. In some contexts, street sex work carries more risk than indoor venues, while the reverse has also been shown 11 53.…”
Section: Discussionmentioning
confidence: 96%
“…This difference was not entirely consistent, suggesting that community-level factors shaping the local organisation of sex work in turn shape health behaviours 6. In some contexts, street sex work carries more risk than indoor venues, while the reverse has also been shown 11 53.…”
Section: Discussionmentioning
confidence: 96%
“…In Guatemala, HIV prevalence in the general population is 0.79 %, and is considerably higher (4.5 %) among female sex workers (FSWs) [2][3][4]. Due its strategic geographical position between Mexico and the rest of Central America [5][6][7], Guatemala is characterized by a significant population of internal [8,9] and international migrants [10], among whom social and structural factors including mobility, gender-based inequalities, migration status, poverty, marginalization, and social exclusion have been linked to increased HIV risk [7,[11][12][13][14]. However, limited evidence is available regarding other structural factors (i.e., public policies and public health regulations surrounding sex work) and their impacts on HIV risk among migrant FSWs.…”
Section: Introductionmentioning
confidence: 99%
“…Whereas empirical research has demonstrated that female migrants are especially vulnerable to HIV/STIs [11,29,30], the ways in which public health practices surrounding sex work and related structural factors (e.g., police abuse) impact migrant FSWs' well-being remain poorly understood. As human rights concerns have been raised regarding how public health practices affect FSWs' well-being [31][32][33], we carried out this study to explore how the implementation of public health practices surrounding sex work (Regulation for the Control of Sexually Transmitted Diseases, Guatemala) shape HIV prevention and care among migrant FSWs in two Guatemalan communities that [5][6][7] are characterized by an important population of internal and international migrants [8,10].…”
Section: Introductionmentioning
confidence: 99%
“…Women seeking a better livelihood often migrate to improve their economic situation, for reasons including economic and gender disparities, subsistence needs, family obligations, and a desire for social mobility. Some women may migrate for the purposes of sex work, whereas others may enter sex work during or following migration for reasons such as remittance pressures and limited formal sector employment opportunities[5-9]. …”
Section: Introductionmentioning
confidence: 99%
“…Female migrants in many lower-income settings – especially those who engage in sex work – often experience substantial health-related vulnerabilities, including HIV and STIs, violence, and poor reproductive health[11,13-21]. However, a recent systematic review among female sex workers (FSWs) identified substantial heterogeneity in the health consequences of migration.…”
Section: Introductionmentioning
confidence: 99%